Analisis Kompensasi dan Beban Kerja Serta Dampaknya Pada Kinerja Pegawai Medis Pada RSUD Bangkinang - Norawati, Suarni; Zulher, Zulher; Yunita, Ani; Ilyas, Ilyas (School of Business, Bogor Agricultural University (SB-IPB), 2022)
RSUD Bangkinang is one of the institutions providing public health services. Medical personnel are the spearhead in providing health services to the community. Therefore, they are required to be professional in carrying out their duties so that the performance of medical personnel continues to increase. This research is necessary, because the division of tasks carried out is still not optimal and there there is often some untimely financial compensation, which may cause the low performance of the medical staff. The purpose of this study was to determine and analyze the effect of compensation and workload variables on the performance of medical employees with civil servant status at Bangkinang Hospital. Employees with the status of civil servants in the medical department at Bangkinang Hospital totaling 100 people, and all of them participated in this study. Hypothesis testing is done by using the F test and t test obtained from the multiple linear regression equation model. The conclusion of this study is that compensation and workload variables have a significant effect on the performance of medical employees with civil servant status at Bangkinang Hospital, both together and individually. From the results of the study it is also known that compensation has a dominant influence on the performance of medical personnel. Compensation and workload variables have a strong relationship with employee performance, which is 83.9%. Variations up or down employee performance by 69.8% is determined by the variable compensation and workload. Keywords: compensation, medical personnal, performance, regression, workload